Faktor-Faktor yang Berpengaruh pada Profitabilitas Perbankan - Afrizal Elgi; Tasya Sastrawati Bumantara; Winda Anggreni Br. Sembiring (IPM2KPE, 2023)
This study aims to explain the effect of cost efficiency, non-interest income, capital adequacy, and credit risk on bank profitability. This research method is quantitative. The sample used in this research is conventional banking that is listed on the Indonesia Stock Exchange during the period 2017 to 2021 with a total sample of 37 banks and a total of 185 units of analysis. This study uses panel data regression to analyze the data. The results showed that the regression equation was ROAit = 0.041478 – 0.564734CEFit + 0.735051NIIit – 0.021278CARit + 0.038834CRit. The coefficient of determination is 38.79%, which means that the independent variable is able to explain the variation of the dependent variable by 38.79% and the remaining 61.21% is influenced by other factors not included in the research model. In conclusion, cost efficiency, non-interest income, and capital adequacy have a significant effect on bank profitability. Keywords: Cost Efficiency, Capital Adequacy, Non-interest Income, Profitability, Credit Risk